Experience and its Narrativization in Oral. History - Herodotus' "Histories" - Wieżel, Iwona (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
In the present article the problem of experience and its narrativization in ancient historiographical texts is discussed. The teleological outline of the Histories as proved by Grethlein (2013), leading to reexperiencing the past on the part of the text recipient, strengthens the present approach to the natural and experiential characteristics of Herodotus’ stories (cf. Labov 1972). Also the performative valour of the examples cited in this paper suggests the possible emotional engagement of the listener/reader of the stories. This engagement is primarily based on the religious bias towards to theion, which actively ffects the lives of the protagonists in the course of the events told. The provenience of the stories within the Histories is mainly oral, which sheds light on the form and structure of this text towardsthe natural (Fludernik 1996) and oral mode of gathering the historical data by the historian, and the presumptive oral proclamation of some parts of the Histories in front of the audience.
Keywords: Herodotus; The Histories; narrativization; experience; natural narratology